Splicing factor hnRNPA2B1 contributes to tumorigenic potential of breast cancer cells through STAT3 and ERK1/2 signaling pathway. Issue 3 (March 2017) - Hu, Ying; Sun, Zihan; Deng, Jinmu; Hu, Baoquan; Yan, Wenting; Wei, Hongyi; Jiang, Jun
Increasing evidence has indicated that the splicing factor hnRNPA2B1 plays a direct role in cancer development, progression, gene expression, and signal transduction. Previous studies have shown that knocking down hnRNPA2B1 in breast cancer cells induces apoptosis, but the mechanism and other functions of hnRNPA2B1 in breast cancer are unknown. The goal of this study was to investigate the biological function, clinical significance, and mechanism of hnRNPA2B1 in breast cancer. The expression of hnRNPA2B1 in 92 breast cancer and adjacent normal tissue pairs was analyzed by immunohistochemical staining. Stable clones exhibiting knockdown of hnRNPA2B1 via small hairpin RNA expression were generated using RNA interference technology in breast cancer cell lines. The effects of hnRNPA2B1 on cell proliferation were examined by MTT and EdU assay, and cellular apoptosis and the cell cycle were examined by flow cytometry. A nude mouse xenograft model was established to elucidate the function of hnRNPA2B1 in tumorigenesis in vivo. The role of hnRNPA2B1 in signaling pathways was investigated in vitro. Our data revealed that hnRNPA2B1 was overexpressed in breast cancer tissue specimens and cell lines. Knockdown of hnRNPA2B1 reduced breast cancer cell proliferation, induced apoptosis, and prolonged the S phase of the cell cycle in vitro. In addition, hnRNPA2B1 knockdown suppressed subcutaneous tumorigenicity in vivo. On a molecular level, hnRNPA2B1 knockdown decreased signal transducer and activator of transcription 3 and extracellular-signal-regulated kinase 1/2 phosphorylation. We concluded that hnRNPA2B1 promotes the tumorigenic potential of breast cancer cells, MCF-7 and MDA-MB-231, through the extracellular-signal-regulated kinase 1/2 or signal transducer and activator of transcription 3 pathway, which may serve as a target for future therapies.